Let $f :X \to Y$ be a continuous map of spaces show the following conditions are equivalent

  1. $f_* : H_n( X) → H_n(Y)$ is an isomorphism for all $n \geq 0$

  2. $f^* :H^n(Y,\mathbb{Z}) \to H^n(X,\mathbb{Z})$ is an isomorphism for all $n \geq 0$.

I think I need to use universal coefficient theorem and the theorem below

if $G$ is an abelian group such that $\text{Hom}(G,Z)=0$ and $\text{Ext}(G,Z)=0$ then $G=0$.

But I cannot write down the details.


By naturality of the universal coefficient theorem for cohomology, $f$ induces a ladder diagram that looks like

$$\require{AMScd} \begin{CD} 0 @>>> \operatorname{Ext}(H_{n-1}(X),\mathbb{Z}) @>>> H^n(X,\mathbb{Z}) @>>> \operatorname{Hom}(H_n(X),\mathbb{Z}) @>>> 0\\ @. @A{\cong}AA @AAA @A{\cong}AA @.\\ 0 @>>> \operatorname{Ext}(H_{n-1}(Y),\mathbb{Z}) @>>> H^n(Y,\mathbb{Z}) @>>> \operatorname{Hom}(H_n(Y),\mathbb{Z}) @>>> 0\\ \end{CD}$$

So by the (short) five lemma, the middle arrow is an isomorphism when $f_*:H_n(X) \to H_n(Y)$ is.

For the converse, see Isomorphism on Cohomology implies isomorphism on homology.

  • $\begingroup$ I can understand your answer, but the link you give about converse, I still cannot understand. $\endgroup$ – noname1014 May 15 '17 at 4:48

Note that $(1)$ is equivalent to $\tilde H_*(M_f)=0$ and $(2)$ is equivalent to $\tilde H^*(M_f)=0$ where $M_f$ is the mapping cylinder of $f$.

Now use universal coefficients and your theorem to conclude the implication $(2)\implies (1)$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for?Browse other questions tagged or ask your own question.